Characteristics of the techniques of skilled female junior athletes in 10 km race walking - Sovenko, S.; Danilyuk, D. (Slovak Journal of Sport Science, 2017)
The paper presents the major kinematic characteristics of the techniques of skilled female junior athletes in 10 km race walking (n = 20, number of results - 32). Comparative analysis of athletes with different level of sports mastery has been carried out. It has been revealed that for the level of results of x = 50:29 (S = 01:14), the average velocity at distance segments constitutes 3.30 m·s-1 (S = 0.09), the average index of stride length is equal to 1.02 m (S = 0.03), whereas the stride frequency and support phase duration - 3.24 stride·s-1 (S = 0.10) and - 0.282 s (S = 0.013), respectively. The angle of foot placement was equal to 70.48º (S = 3.22), whereas that of take-off - 58.09º (S = 1.93).